Socio-Spatial Theory in Nordic Geography Intellectual Histories and Critical Interventions - Jakobsen, Peter; Jönsson, Erik; Larsen, Henrik Gutzon (Springer Nature, 2022)
This open access book is about socio-spatial theory in, and the nature of, Nordic geography. From both historical and contemporary perspectives, the book engages with theorisations of geography in the Nordic countries. Including chapters by geographers from Denmark, Finland, Iceland, Norway and Sweden, it reflects how theories about the relations between the social and the spatial have been developed, adopted and critiqued in Nordic human geography in relation to a wide range of themes, concepts and approaches. The book also traces institutional developments, distinct geographical traditions and intellectual histories, as well as authors' own experiences as geographers in and beyond the Nordic area. The chapters together introduce and engage with debates and discussions that permeate Nordic geography and allows readers a glimpse of geographical thinking and the role of socio-spatial theory in the Nordic countries. By providing insights into how geographical ideas emerge, travel and are translated and adapted in specific contexts, the book contributes to debates about historical-geographical situatedness and theorisations of geography.